Catalysis without precious metals - Bullock, R. Morris (Weinheim : Wiley-VCH, 2010)
Written for chemists in industry and academia, this ready reference and handbook summarizes recent progress in the development of new catalysts that do not require precious metals. The research thus presented points the way to how new catalysts may ultimately supplant the use of precious metals in some types of reactions, while highlighting the remaining challenges. An essential companion for organic and catalytic chemists, as well as those working with/on organometallics, and graduate students.
6: Cobalt and Nickel Catalyzed Reactions Involving CH and CN Activation Reactions7: A Modular Approach to the Development of Molecular Electrocatalysts for H2 Oxidation and Production Based on Inexpensive Metals; 8: Nickel-Catalyzed Reductive Couplings and Cyclizations; 9: Copper-Catalyzed Ligand Promoted Ullmann-typeCoupling Reactions; 10: Copper-Catalyzed Azide-Alkyne Cycloaddition (CuAAC); 11: "Frustrated Lewis Pairs" : A Metal-Free Strategy for Hydrogenation.
Includes bibliographical references and index.
Print version record.
Keywords: Catalysts; Catalysis; Science; Science: Chemistry; SCIENCE -- Chemistry -- Physical & Theoretical; Catalysis; Catalysts; Electronic books